Cross‐field current instability for auroral bead formation in breakup arcs - A. T. Y. Lui (Geophysical Research Letters)
Abstract The physical process responsible for the onset of substorm expansion is still unresolved in spite of decades of research on the topic. Detailed properties of the spatially periodic auroral beads on prebreakup auroral arcs that initiate substorm expansion onset are now available. These auroral bead properties impose severe observational constraints on the onset process. In this work, theoretical predictions of the cross‐field current instability are evaluated in terms of these constraints. The growth rates and wavelengths associated with auroral beads in several previously published events are reproduced by the cross‐field current instability, implying that the instability can indeed account for the characteristics of auroral beads that eventually lead to substorm onset. The present results differ from the conclusion reached by a previous analysis that the shear flow ballooning instability can account for the growth and spatial scales of auroral beads better than the cross‐field current instability.